THE INSTITUTIONALIZATION OF UKRAINIAN BUREAUCRACY IN THE PROCESS OF STATE BUILDING - Краснова, М.Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The problem of bureaucratic state apparatus is one of the most pressing in our country. The article defines the concept of bureaucracy deals with basic theoretical foundations of this phenomenon. Features of the bureaucratic process in modern Ukraine and its negative effects on the development of democratic principles and civil society. Considerable attention is given to ways of overcoming bureaucracy in Ukraine.